The process of loading and displaying documents of Antarctic research based on BLOB STORAGE - Omelchenko, A.I.; Globa, L.S.; Moroz, I. V. (Ukrainian Antarctic Journal, 2016)
The work is dedicated to increasing the structuring, storage reliability and fast access to data of Antarctic Research of the National Antarctic Data Centre based on Azure BLOB Storage technology from Microsoft. The analysis of the indicators to determine the access efficiency to “cloud resources,” to find the main criteria. A detailed over view of the main features of “cloud” storage technologies from Microsoft is presented. The basic definition of storage technology BLOB-objects is determined. Data loading algorithms for State Institutions National Antarctic Scientific Center in Azure storage and their submission are proposed.